Implementation of Educational Technology in Learning at Madrasah Aliyah Negeri 2 Palembang - Nyayu Khodijah; Ahmad Zainuri; Ibrahim Ibrahim (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The purpose of this research is to determine how educational technology is implemented in the learning process at Madrasah Aliyah Negeri 2 Palembang. This research is a type of qualitative research with a descriptive approach. In this study, the informants were school principals, students, education staff, and others related to this research. Data collection techniques, namely through the method of observation, interviews, and documentation. Data analysis techniques in this study used data reduction, data presentation, and verification, and also, there was a technique for checking the validity of data through triangulation. The results of this study indicate that the educational technology used in learning covers all subjects, and all teachers are free to use existing educational technology and can even develop it according to the needs of existing learning. In implementing educational technology in learning, MAN 2 Palembang has implemented a systems approach as an integral part of the education process. This system is well built in the learning process by utilizing educational technology. Besides that, MAN 2 Palembang has also carried out a learning process oriented towards students. This is important to implement so that what is the need of students can be adequately accommodated by madrasas. What is no less important is the use of good learning resources to achieve educational goals.